An Unusual Cause of Coma - Sujith Ovallath; R. S. Raj; Abdu Rahman; A. S. Girija (Case Reports in Medicine)
This case report is an unusual presentation of fibroid uterus as coma. The patient developed a recurrent hypoglycemia possibly secondary to the insulin-like growth factor secreted from the fibroid. The hypoglycemic symptoms disappeared on removal of the fibroid. The histopathological examination revealed no evidence of malignancy.